Spiritually Motivated Self-Forgiveness and Divine Forgiveness, and Subsequent Health and Well-Being Among Middle-Aged Female Nurses: An Outcome-Wide Longitudinal Approach - Long, Katelyn N. G.; Chen, Ying; Potts, Matthew; Hanson, Jeffrey; VanderWeele, Tyler J. (Frontiers in Psychology, 2020)
Background: Interest in the relationship between forgiveness and health is steadily growing across disciplines within the research community. While there are multiple forms of forgiveness, past research has focused principally on studying forgiveness of others, whereas longitudinal evidence on the associations between other forms of forgiveness and health remains scarce. Methods: Using longitudinal data from the Nurses’ Health Study II (from the 2008 Trauma Exposure and Post-traumatic Stress Supplementary Survey to 2015 questionnaire wave), this study employed an outcome-wide analytic approach to prospectively examine the association between two forms of religiously or spiritually motivated forgiveness, namely self-forgiveness and divine forgiveness, and a wide array of subsequent psychosocial well-being, mental health, health behavior, and physical health outcomes among middle-aged female nurses (N=54,703 for self-forgiveness; N=51,661 for divine forgiveness). All models controlled for sociodemographic factors, prior religious service attendance, and prior values of all outcome variables wherever data were available. Bonferroni correction was used to account for multiple testing. Results: Self-forgiveness was strongly associated with greater psychosocial well-being (e.g., for top versus bottom level of self-forgiveness, β=0.23, 95% CI: 0.20, 0.25 for positive affect) and lower psychological distress (e.g., β =-0.21, 95% CI: -0.23, -0.18 for depressive symptoms). To a lesser extent, divine forgiveness was also associated with higher levels of psychological well-being and lower psychological distress. For both forgiveness types, there was little evidence of association with physical health or health behavior outcomes, though possible marginal evidence for an association of self-forgiveness with increased mortality. Discussion: This study provides novel evidence that religiously or spiritually motivated self-forgiveness and divine forgiveness are both positively related to several indicators of psychosocial well-being and inversely associated with psychological distress outcomes, whereas the associations with physical health and health behaviors are less clear. Further longitudinal investigation of the dynamics between these types of forgiveness and health and well-being is warranted.